IMPROVING STUDENT LEARNING OUTCOMES THROUGH THE USE OF ANDROID-BASED MEDIA AND LEARNING MOTIVATION - Khasanah khasanah; Moh Fahri Yasin; Arifin Budiana (Akademika : Jurnal Teknologi Pendidikan, 2022)
This study aims to determine 1) The positive relationship between the use of android-based media and the learning outcomes of Indonesian students at grade XI 2) The positive relationship between learning motivation and learning outcomes for students at grade XI 3) the Positive relationship between the use of android-based media and learning motivation together -the same as the results of learning Indonesian students at grade XI. This study uses a survey method. The sampling technique used a random sampling technique so that the sample size was 100 respondents. The collection of data on learning outcomes uses document data and learning motivation using an instrument in the form of a questionnaire. Then the data analysis technique used analysis regresi. The results showed. There is a positive relationship between the use of android-based media and the learning outcomes of students at grade XI 2) There is a positive relationship between learning motivation and learning outcomes of students at grade XI 3) There is a positive relationship between the use of Android-based media and learning motivation -the same as the Indonesian learning outcomes students at grade XI.